A SPICE model of an antenna for transmitting. Issue 2 (24th April 2014) - Gao, Xiang; Du, Zhengwei
Abstract : A SPICE model of an antenna for transmitting is proposed. This model allows for the calculation of the frequency-domain radiation fields for a range of frequencies in which the model is valid, it also allows for the direct calculation of the time-domain (TD) radiation fields for an arbitrary TD excitation signal, the spectrum of which should be within the modeling range. The model is then verified by two examples, both of them demonstrate its validity. This model can be a part of a complete system-level model for electromagnetic compatibility simulation.